Efficacy and Safety of Different Doses of Bevacizumab Combined With Pemetrexed and Platinum in First-Line Treatment of Advanced NSCLC: A Retrospective-Real World Study - Zhou, Chun-Hua; Yang, Feng; Jiang, Wen-Juan; Zhang, Yong-Chang; Yang, Hai-Yan; Zeng, Liang; Liu, Li; Xiong, Yi; Zeng, Fan-Xu; Wang, Zhan; Yang, Nong (Frontiers in Pharmacology, 2021)
Background: Bevacizumab was demonstrated to have efficacy in patients with NSCLC. However, application of different doses of bevacizumab in different clinical trials was overlooked. This study aims to investigate the effects and safety of different doses of bevacizumab in the treatment. Methods: From January 2016 to March 2020, 79 patients with NSCLC received first-line combination treatment with chemotherapy (pemetrexed+platinum) and bevacizumab for 4 cycles, patients without progression after four cycles were randomly assigned to maintenance therapy with bevacizumab combined with pemetrexed, of which 57 patients received bevacizumab at a dose of 7.5 mg/kg and 22 patients at a dose of 15 mg/kg. The primary endpoint was progression‐free survival, and secondary endpoints were overall response rate, disease control rate, and adverse events. Results: There was no significant difference between two groups in effectiveness; Median PFS in 7.5mg/kg group and in 15mg/kg group were 8.0 and 8.7months, respectively (P = 0.663). reaching the primary endpoint. The ORR and DCR in the bevacizumab 7.5 mg/kg group were 45.46% and 86.0% vs 50% and 90.9% was no statistical significance (P = 0.804 and 0.717). Most of side effects were tolerable. The incidences of overall toxicities were higher in 15mg/kg group. No new safety signals were observed. Conclusion: The administration of 7.5mg/kg was non‐inferior to 15mg/kg, the cost-effectiveness of the 7.5 mg/kg group was significantly better than that of the 15 mg/kg group.